An Analysis of the Translation of a Scientific Article entitled Fiction from the Periphery: How Dutch Writers Enter the Field of English Language Literature - Rinta Sukma Firdaus, Mei; Widyasari (Smart Edu Center, 2023)
Literary translations throughout the world are mostly made from English, so a translator is needed to translate into other languages. Translation is defined as the process of transferring a source language message (TL) into the target language (TL) in an equivalent manner. Translation of the journal entitled